2017
DOI: 10.1016/j.redox.2016.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose does not improve neuronal survival on exposure to alpha-synuclein pre-formed fibrils

Abstract: Parkinson's disease is a debilitating neurodegenerative disorder that is pathologically characterized by intracellular inclusions comprised primarily of alpha-synuclein (αSyn) that can also be transmitted from neuron to neuron. Several lines of evidence suggest that these inclusions cause neurodegeneration. Thus exploring strategies to improve neuronal survival in neurons with αSyn aggregates is critical. Previously, exposure to αSyn pre-formed fibrils (PFFs) has been shown to induce aggregation of endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
(45 reference statements)
1
27
0
Order By: Relevance
“…Various studies have shown that exogenous application of α-synuclein preformed fibrils (PFFs) promotes the formation of protein aggregation in cells (Luk et al, 2012;Volpicelli-Daley et al, 2011). Interestingly, it has been shown that when primary cortical neurons are treated with trehalose alone, the LC3-II levels increase and remained elevated on treatment with both trehalose and α-synuclein PFFs, whereas no significant changes were observed in the levels of aggregated α-synuclein, indicating that PFFs were resistant to degradation even with augmentation of macroautophagy (Table 1; Redmann et al, 2017).…”
Section: ;mentioning
confidence: 99%
“…Various studies have shown that exogenous application of α-synuclein preformed fibrils (PFFs) promotes the formation of protein aggregation in cells (Luk et al, 2012;Volpicelli-Daley et al, 2011). Interestingly, it has been shown that when primary cortical neurons are treated with trehalose alone, the LC3-II levels increase and remained elevated on treatment with both trehalose and α-synuclein PFFs, whereas no significant changes were observed in the levels of aggregated α-synuclein, indicating that PFFs were resistant to degradation even with augmentation of macroautophagy (Table 1; Redmann et al, 2017).…”
Section: ;mentioning
confidence: 99%
“…Whilst it has been suggested that its ability to reduce protein aggregation occurs due to a chaperone activity, or through binding and stabilization of abnormal proteins ( Tanaka et al, 2004 ; Davies et al, 2006 ), it has also been shown to act via an mTOR-independent pathway to increase autophagy ( Sarkar et al, 2007 ; Rodríguez-Navarro et al, 2010 ). These studies have clearly prompted interest in this compound, though a recent study of mouse primary cortical neurons found that trehalose did not prevent toxicity from exposure to α-synuclein pre-formed fibrils ( Redmann et al, 2017 ).…”
Section: α-Synuclein As a Therapeutic Targetmentioning
confidence: 99%
“…[38][39][40][41][42][43][44] PFF-induced α-syn inclusions resemble LBs in that they are compact intracytoplasmic structures of hyperphosphorylated (ser129) α-syn (psyn), co-localize with ubiquitin and p62, and are thioflavin-S-positive and proteinase-k Western blotting: Western blots for α-syn, DAT and VMAT2 were carried out as previously described. 33,39,42,[59][60][61] Striatal tissue punches were homogenized in tissue lysis buffer (Tris buffered saline with 1% SDS) and centrifuged at 1150 x g for 5 minutes at 4˚C. Protein levels were quantified by BCA protein assay.…”
Section: Introductionmentioning
confidence: 99%